The Development and Evaluation of a Loop-Mediated Isothermal Amplification Method for the Rapid Detection of Salmonella enterica serovar Typhi - Fan, Fenxia (PLoS One, 2015)
Typhoid fever remains a public health threat in many countries. A positive result in traditional culture is a gold-standard for typhoid diagnosis, but this method is time consuming and not sensitive enough for detection of samples containing a low copy number of the target organism. The availability of the loop-mediated isothermal amplification (LAMP) assay, which offers high speed and simplicity in detection of specific targets, has vastly improved the diagnosis of numerous infectious diseases. However, little research efforts have been made on utilizing this approach for diagnosis of Salmonella enterica serovar Typhi by targeting a single and specific gene. In this study, a LAMP assay for rapid detection of S. Typhi based on a novel marker gene, termed STY2879-LAMP, was established and evaluated with real-time PCR (RT-PCR). The specificity tests showed that STY2879 could be amplified in all S. Typhi strains isolated in different years and regions in China, whereas no amplification was observable in non-typhoidal strains covering 34 Salmonella serotypes and other pathogens causing febrile illness. The detection limit of STY2879-LAMP for S. Typhi was 15 copies/reaction in reference plasmids, 200 CFU/g with simple heat-treatment of DNA extracted from simulated stool samples and 20 CFU/ml with DNA extracted from simulated blood samples, which was 10 fold more sensitive than the parallel RT-PCR control experiment. Furthermore, the sensitivity of STY2879-LAMP and RT-PCR combining the traditional culture enrichment method for simulated stool and blood spiked with lower S. Typhi count during the 10 h enrichment time was also determined. In comparison with LAMP, the positive reaction time for RT-PCR required additional 2-3 h enrichment time for either simulated stool or blood specimens. Therefore, STY2879-LAMP is of practical value in the clinical settings and has a good potential for application in developing regions due to its easy-to-use protocol.